Optimalisasi Pendidikan Anak dalam Keluarga melalui Kitab Tarbiyatul Athfal - Chusna, Mufidatul; Zulfahmi, Muhammad Nofan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Most parents, when raising their children, just provide for their needs like clothes, food, and shelter, and try to make their children smart and sharp in their thinking. Although that alone is not enough for life, parents need to shape their children to have good ethics and wisdom so that the children do not despair and have a clear purpose in life through studying the book Tarbiyatul Athfal. The issue in this writing is how to maximize early childhood education in the family based on the Islamic perspective. This writing uses a descriptive qualitative research strategy and in presenting the creator's information, it uses documentation, interviews, and observations to obtain applicable information. The results of this research show that there are several ways that can be utilized to enhance children's education in the family through the book Tarbiyatul Athfal, especially based on the Islamic view, namely: 1) Model or example strategy, 2) Habituation strategy, 3) Giving advice, 4) Consideration and management techniques, 5) Discipline strategy. If these methods are viewed and applied from an Islamic perspective, they will greatly help parents in educating their children from an early age about good morals.